EMPOWERMENT OF QUALITY DEVELOPMENT OF STUDENT HUMAN RESOURCE ASSETS IN THE SITI KHADIJAH STUDENT COMMUNITY OF AL-QODIRI ISLAMIC BOARDING SCHOOL JEMBER IN DEVELOPING THE CREATIVITY AND PRODUCTIVITY OF STUDENTS IN 2021 - Alfian Izzat El Rahman (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2022)
Santri in Islamic boarding schools finds to seek knowledge and become agents of civilization in society. Therefore, students are to be creative and innovative in all things, including developing skills in terms of economic business. Empowerment in the Community of Santri Siti Khadijah Pondok Pesantren Al-Qodiri Jember by using the Asset Based Community Development (ABCD) method can unlock the keys that: 1) develop the quality of students in optimal creativity and productivity; 2) development of the quality of the students of the Siti Khadijah dormitory in terms of optimal understanding and practice of making mask connectors; 3) development of the quality of students in the aspects of understanding and practice of making traditional foods in the form of skirts korok, cenil, lapis, lanon, etc., optimally; 4) quality development in the aspect of understanding the benefits of plants and the practice of making traditional herbal medicine runs optimally. Overall, this empowerment program runs optimally and will not succeed if there is no cooperation and active participation from the subject of mentoring, the community, especially the surrounding community.